ANALISIS KINERJA GURU DAN HAMBATAN DALAM PELAKSANAAN PEMBELAJARAN TEMATIK DI SD SWASTA ISLAM PERWIS-SKM PADANGDISIMPUAN - Laila Alfi Sahri Lubis; Salsabila harahap; Rama Nida Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze teacher performance and the obstacles faced in implementing thematic learning SD Swasta Islam PERWIS-SKM Padangsidimpuan. The study used a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation of grade III and VI teachers. The results of the study indicate that teacher performance in planning, implementing, and assessing thematic learning has been running quite well, demonstrated by teachers' efforts in preparing lesson plans based on the 2013 Curriculum, implementing varied learning methods such as discussions, questions and answers, presentations, and outdoor learning, and providing evaluation through observation and assessment of student work. However, several obstacles were still found, such as difficulties in integrating between subjects, limited learning facilities, differences in student abilities, and administrative burdens that reduce planning time. Teachers attempted to overcome these obstacles through media modifications, collaboration with other teachers, adjustments to learning methods, and additional assistance for students who needed it. The results of this study emphasize the importance of school facility support and ongoing training to improve the effectiveness of thematic learning implementation in elementary schools.